(untitled) (Construction Economics and Building, 2025)
The current study examines the impact of perceived organizational politics on employee organizational withdrawal dimensions within the construction sector, a field characterized by a challenging work environment and high employee turnover. Grounded in Equity Theory, the research examines the moderating role of gender in the relationship between perceived organizational politics and psychological and physical withdrawal behaviors. Data from 318 construction professionals were collected through a quantitative survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that perceived organizational politics significantly influences withdrawal behaviors, with female professionals showing a greater tendency to disengage compared to their male counterparts. This research contributes original insights to the construction management literature by highlighting the gendered effects of organizational politics on employee withdrawal, a previously underexplored area. The study underscores the critical need for organizations to address political dynamics in the workplace to foster a fair and supportive environment, ultimately enhancing employee well-being and organizational performance.